Integral Human Development: From Paternalism to Accompaniment - Pope, Stephen J. (Theological studies, 2019)
This article traces the development of Catholic treatments of integral human development from Paul VI's Populorum Progressio to the writings of Pope Francis on accompaniment. The author argues that community organizing is an important avenue for promoting the political dimension of accompaniment as understood in the teaching of Pope Francis.